2022
DOI: 10.1002/aelm.202200065
|View full text |Cite
|
Sign up to set email alerts
|

Operation Mechanism of n‐Type Organic Electronic Metabolite Sensors

Abstract: The integration of n‐type (electron‐transporting) polymers with oxidase enzymes has allowed building high‐performance organic electrochemical transistor (OECT) based metabolite sensors. Yet, the operation mechanism of these devices is poorly understood. Here, the process is investigated for the conversion of metabolite oxidation to electrical current in an n‐type organic electrochemical transistor (n‐OECT). By monitoring oxygen (O2), hydrogen peroxide, and pH changes in the electrolyte as well as the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 41 publications
3
24
0
Order By: Relevance
“…Prior to all electrochemical experiments, p(NDI-T2 P75) was purified to remove residual Pd contamination from polymer synthesis (Figure S1, Table S1), resulting in low Pd concentrations of 2 -5 ppm. While it has been reported that a polymer much like p(NDI-T2 P75) primarily produces H2O upon reducing O2 in a 4-electron reaction, 46 we demonstrate that the removal of residual Pd is crucial for evaluating the performance of the polymer itself without Pd contributing to ORR performance. Higher concentrations of Pd shift the measured halfwave voltage, E1/2, for oxygen reduction and change whether H2O or H2O2 is the majority product (Figure S2).…”
Section: Understanding the Electrochemistry Of P(ndi-t2 P75)mentioning
confidence: 59%
“…Prior to all electrochemical experiments, p(NDI-T2 P75) was purified to remove residual Pd contamination from polymer synthesis (Figure S1, Table S1), resulting in low Pd concentrations of 2 -5 ppm. While it has been reported that a polymer much like p(NDI-T2 P75) primarily produces H2O upon reducing O2 in a 4-electron reaction, 46 we demonstrate that the removal of residual Pd is crucial for evaluating the performance of the polymer itself without Pd contributing to ORR performance. Higher concentrations of Pd shift the measured halfwave voltage, E1/2, for oxygen reduction and change whether H2O or H2O2 is the majority product (Figure S2).…”
Section: Understanding the Electrochemistry Of P(ndi-t2 P75)mentioning
confidence: 59%
“…Since the ntype OECT current is inherently sensitive to changes in the O 2 content of its environment, the GOx reaction with glucose led to an immediate increase in I D . 25 Although all polymers are sensitive to O 2 and all polymers except P-ZI operated sufficiently as an OECT, only P-90, P-100, and P-100B OECTs showed a current response to the oxidation of glucose (Figure 2a). Figure 2b compares the glucose sensitivity of these devices (NR OECT ).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…As glucose was oxidized by GOx, the O 2 amount in the electrolyte decreased as it was used for GOx regeneration. Since the n-type OECT current is inherently sensitive to changes in the O 2 content of its environment, the GOx reaction with glucose led to an immediate increase in I D . Although all polymers are sensitive to O 2 and all polymers except P-ZI operated sufficiently as an OECT, only P-90, P-100, and P-100B OECTs showed a current response to the oxidation of glucose (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations